Growth inhibition of P. aeruginosa by methanol extract of Bridelia stipularis and identification of active components using in silico studies - A. Sini; T. K. Bindu; Vinod P. Raphael; K. S. Shaju; Sherry Sebastian (SpringerOpen, 2024)
Abstract Background Antimicrobial resistance among pathogens is an emerging problem, gaining significant importance recently. Pharmaceutical scientists are constantly exploring innovative and effective antibacterial agents. Pseudomonas aeruginosa (P. aeruginosa) is a bacterium primarily responsible for pneumonia and infections in the liver, kidneys, and other body parts. It is a Gram-negative bacterium that can be controlled by antibiotics such as ciprofloxacin and levofloxacin. However, this pathogen sometimes exhibits resistance to these antibacterial agents. Methods Recognizing the well-known potential of plants as sources of medicinal compounds, our study focused on the ethyl acetate, acetone and methanol extract of the leaves of Bridelia stipularis and its impact on the growth of P. aeruginosa using well diffusion method. To gain insight into the composition of the extract, we conducted GC-MS analysis. After identifying the components present in the extract, we assessed the drug-likeness, absorption, distribution, metabolism, and excretion (ADME) and conducted docking studies of the molecules with the selected structural receptors of P. aeruginosa to find out the active component present in the extract. Results Remarkably, only methanol extract of Bridelia stipularis demonstrated significant antibacterial activity against this pathogen. In silico investigations revealed that two compounds, namely ethyl iso-allocholate and toluene sulfonylhydrazone derivative, exhibited high inhibition potencies. All structural receptors of the pathogen taken for this study were well inhibited by ethyl iso-allocholate while the receptors such as laconizing lipase and penicillin-binding protein of the bacterium were bound well with the 4-phenyl-3-penten-2-one p-toluene sulfonylhydrazone. Conclusions Observations of this study clearly establish that the two phytochemicals present in the methanolic extract, i.e., ethyl iso-allocholate and toluene sulfonylhydrazone derivative of Bridelia stipularis leaves are highly active against the growth of the opportunistic pathogen P. aeruginosa. Graphical abstract